Weave inter-barangay urban agricultural network through barangays Molino III and Molino IV - Placido, Derik D.; Galingan, Zenaida D. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The last century has seen the steady increase of urban populations in different parts of the world. Through the latter part of the 20th century up to the present, this trend of rural flight, or the shift of populations from rural to urban areas, can be said to have accelerated. More recently, the improvement of agriculture in rural areas has caused local populations to seek other opportunities in the cities. The Philippines is no exception to this trend. Between 1960 and 1990, the urban population had increased from 30 to over 48 percent. Although that percentage has been declining since then, still nearly half of the Philippines population (44 percent) resides in urban areas. With that said, urbanization brings with it a number of issues. These include increased demand for basic services such as sanitation, resource scarcity (Veenhuizen, 2006), reduction of green areas, and the urban heat island effect, among others. Bacoor, which is among the Philippine's rising metropolises, is one of many cities that are seeing the effects of urbanization. In this study, urban agriculture will be used as a tool to counter the issues that accompany this worldwide phenomenon. Landscape architecture will be employed to create a development spanning two barangay centers, connected by a green corridor to provide more productive and green areas. Various forms of urban agriculture will serve as the core infrastructures and activities in the proposed urban agricultural park, run by the surrounding communities themselves. Ultimately, this thesis aims to propose a solution to food deficiency that could serve as a model for future initiatives of the same vein.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Urban agriculture